Work Life Balance and Implications for Business Process Outsourcing in India - Roedger, Sam; Pratt, Ellen; Mendez Gandica, Beatris A. (My University, 2013)
Business Process Outsourcing has been the strategic choice of companies looking at visible profits of cost reduction while improving the quality of service (Shah and Sharma 2007). Offering tremendous opportunities to western businesses, the India BPO sector has been emerging rapidly as the place of choice because of the availability of a skilled workforce, English speaking labor force and technically qualified employees. However, there is a flipside to BPOs; there are both challenges, internal and external. The internal challenges include the shortage of competent middle and senior level managers and the high attrition rates in the BPO industry in India. The external challenges include opposition from U.S. politicians and labor unions against the shift of BPO operations to companies in India as well as competition from other countries that are taking away business from India by providing lower cost services. The purpose of this study was to examine the issues related to attrition or turnover in the Indian BPO industry and is grounded in existing theories of work-family balance and turnover intentions of employees.
Color poster with text and tables.
Keywords: Business process outsourcing--India; Attrition--Causes; Turnover--Causes; Work-life balance; Posters